(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
High-resolution additive manufacturing methods such as digital light processing (DLP) offer promising opportunities for rapid tooling for micro injection molding (µIM). There are possible savings in time and costs for µIM of small and micro plastic parts for sensors, electronics and (bio)medical products. Here we present the rapid tooling of polymeric molds via DLP 3D printing for the µIM of convex chips (Ø3.5 x 1.16 mm) of polypropylene (PP) as exemplarily chosen geometry and medical relevant material. Five molds (one mold has a total size of 8 x 22 x 10 mm, height x length x width, made of 2 pieces) were 3D printed simultaneously in t 30 min (plus t = 10 min post-curing) with a layer height of z = 50 µm and a photopolymer consumption of m 2 g per mold. The micro-injection-molded PP chips show a significant staircase-effect as a result of 3D printing of the molds. Nevertheless, the molds perform well (no cracks, adequate demolding) when used for a relatively low number of µIM cycles (n 20, Tmold = 30 °C, TPP = 205 °C).